PENERAPAN MODEL TREFFINGER TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 1 KUBUNG KABUPATEN SOLOK - Angriani, Putri; Anggraini, Villia; Mardiyah, Ainil (Pendidikan Matematika, 2014)
AbstrakThis research was motivated by the less active studentsâ in the learning process of mathematics and students understanding of mathematical concepts is still low. The purpose of this study was to determine the effect of the application of the model to the understanding of mathematical concepts Treffinger students better than students in understanding mathematical concepts with conventional learning, and see the development of student activity in the learning process. This type of research is experimental research design with random on the subject. Population is a eighth grade student SMPN 1 Kubung Kabupaten Â Solok. The instrument used in this study is an essay test . Data were analyzed using the test for normality, homogeneity test and t-test. From the statistical result obtained thitung = 1,713 and is larger than the ttabel =1,682 thus reject H0 which means thank H1. So, it can be concluded that the ability of understanding of mathematical concepts that students use the model Treffinger better than conventional learning eighth grade students SMPN 1 Kubung Kabupaten Solok.